IGF1R facilitates epithelial-mesenchymal transition and cancer stem cell properties in neuroblastoma via the STAT3/AKT axis - Wang XH; Wu HY; Gao J; Wang XH; Gao TH; Zhang SF (Cancer Management and Research, 2019)
Xiao-Hui Wang,1 Hai-Ying Wu,2 Jian Gao,1 Xu-Hui Wang,1 Tian-Hui Gao,3 Shu-Feng Zhang11Department of Pediatric Surgery, People’s Hospital of Zhengzhou University (Henan Provincial People’s Hospital), Zhengzhou 450003, People’s Republic of China; 2Department of Obstetrics, People’s Hospital of Zhengzhou University (Henan Provincial People’s Hospital), Zhengzhou 450003, People’s Republic of China; 3Department of Medical Oncology, People’s Hospital of Zhengzhou University (Henan Provincial People’s Hospital), Zhengzhou 450003, People’s Republic of ChinaBackground: Neuroblastoma (NB) displays the most heterogeneity in clinical manifestation. The insulin-like growth factor 1 receptor (IGF1R) has long been recognized for its role in tumourigenesis and growth. The IGF/IGF1R pathway is important in maintaining cell survival. It is reported that IGF1R participates in the occurrence of NB, but the mechanism is still unclear.Methods: Human NB cell lines IMR-32 and SH-SY5Y were recruited in this study. IGF1R was knocked down by transfection with short hairpin RNA. Signal transducer and activator of transcription 3 (STAT3) expression was inhibited by Cryptotanshinone treatment. Cell proliferation, migration, and invasion were determined by MTT assay, wound healing assay, and cell invasion assay, respectively. The cancer stem cell properties were characterized by tumour sphere formation assay and colony formation assay. The mRNA and protein expression levels of related proteins were detected by RT-PCR and Western blot, respectively.Results: The knockdown of IGF1R inhibits NB cell tumourigenesis and the epithelial-mesenchymal transition (EMT) of NB cells. Additionally, IGF1R was found to stimulate cancer stem cell-like properties in NPC cells. The knockdown of IGF1R significantly reduced the phosphorylation of AKT, and STAT3, indicating that the activation of the AKT and STAT3 pathways was inhibited by IGF1R knockdown. Furthermore, IGF1R was demonstrated to stimulate cancer stem cell-like properties in NB cells via the regulation of the STAT3/AKT axis.Conclusion: IGF1R promotes cancer stem cell properties to facilitate EMT in neuroblastoma via the STAT3/AKT axis.Keywords: IGF1R, neuroblastoma, epithelial mesenchymal transition, stemness, STAT3, AKT